(untitled) (Fiep Bulletin - online, 2014)
The Organic Health Law n°8.080/90 states that the existence of conditioning and determining factors to infectious diseases such as food, housing, sanitation, environment, work, income, formal education, transportation, leisure and access to essential goods and services, characterize health. Most diseases can be avoided with primary prevention, which purpose is to limit the incidence of diseases. The purpose of the research is to identify risk factors among Nursing undergraduates, Unioeste, Foz do Iguaçu/PR. It is across-sectional study, with 120 subjects, undergraduate Nursing students from Unioeste in Foz do Iguaçu, during the firs half of 2012. The data collecting tool focused questions about risk factors and the undergraduates’ socioeconomic profile. Results show 20% of the subjects with overweight, 53% declared having sedentary lifestyle, 5% smoke, while 25,8% declared already used a cigarette, 56% drinks weekly certain amount of alcohol. We may conclude that the number of undergraduates expose to the studied risk factors is high, especially on physical activity. It is conspicuous that the undergraduate needs a supporting group that works on these fragilities, so that diminishes risks and strengthens theory with practice, improving health education.